Thromboinflammation response to tocilizumab in COVID‐19. Issue 8 (18th October 2020) - Gergi, Mansour; Cushman, Mary; Littenberg, Benjamin; Budd, Ralph C.
Abstract: Background: Coronavirus disease‐19 (COVID‐19) spans a wide spectrum of illness. Severe cases of COVID‐19 can manifest inflammation in organs other than the lung, in tissues not known to support viral replication, and also in a hypercoagulable state. These observations have suggested that severe acute respiratory syndrome coronavirus 2 can provoke a hyperimmune response in some cases that could lead to secondary organ damage. Methods: With evidence of elevated levels of interleukin‐6 (IL‐6) in patients with severe COVID‐19, we conducted a small pilot off‐label compassionate care study of the IL‐6 receptor inhibitor tocilizumab in patients with severe COVID‐19. Results: A single infusion of tocilizumab in patients with severe COVID‐19 manifested rapid declines in C‐reactive protein and d ‐dimer and gradual rises in lymphocyte and platelet counts. Conclusions: These findings suggest both pathophysiological mechanisms and clinical benefit that might be seen with IL‐6 inhibition in severe COVID‐19.